2021
DOI: 10.1109/jphot.2021.3106706
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Demonstration of Fiber-Wireless Fronthaul Networks Using a Hybrid Multi-IF-Over-Fiber and Radio-Over-Fiber System

Abstract: This paper reports an end-to-end demonstration of a fiber-wireless mobile fronthaul (MFH) network based on hybrid intermediate-frequency-over-fiber (IFoF) and radio-over-fiber (RoF) links using a 28-GHz millimeter-wave (MMW) band. We successfully transmitted 24 64-QAM OFDM signals with a total bandwidth of 9.12 GHz over 20-km broadband IFoF, 1-km narrowband IFoF, 500-m RoF, and 10-m free-space links with an aggregate capacity of up to 34.2 Gbps, which complies with the required peak data capacity of IMT-2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…If applying different IF to convert each signal streams for MIMO transmission it can be multiplexed by FDM in a single optical fiber, and improves efficiency [68]. In [69], it is demonstrated that 24 streams of 400 MHz bandwidth 5G NR signals are successfully transmitted, and achieved 34.2 Gbps throughput with 9.12 GHz bandwidth over 20 km links. However, the number of the streams corresponding antennas is limited depending on the supporting bandwidth of the devices such as the electrical to optical (E/O) converter and optical to electrical (O/E) converter.…”
Section: Fronthaulingmentioning
confidence: 99%
“…If applying different IF to convert each signal streams for MIMO transmission it can be multiplexed by FDM in a single optical fiber, and improves efficiency [68]. In [69], it is demonstrated that 24 streams of 400 MHz bandwidth 5G NR signals are successfully transmitted, and achieved 34.2 Gbps throughput with 9.12 GHz bandwidth over 20 km links. However, the number of the streams corresponding antennas is limited depending on the supporting bandwidth of the devices such as the electrical to optical (E/O) converter and optical to electrical (O/E) converter.…”
Section: Fronthaulingmentioning
confidence: 99%
“…In [7], a system for the transmission of energy through an optical fiber is proposed. In [8], the functionality of a fiber-radio scheme with different simultaneous transmission frequencies using a digital multiplexer for the selection of frequencies and channels is demonstrated. In [9], a fiber-radio scheme is characterized where a microwave signal provided by a receiving antenna is supplied to an optical modulator.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to mention that no antenna transmission has been realized in [15] or [16]. The low frequency DML was used as well as a low cost solution for intermediate frequency (IF) over fiber (IFoF) transmission in [17], where authors experimentally demonstrated end-to-end fiber wireless fronthaul. The proposed approach introduced a broadband IFoF transmission combined with narrow band IFoF by using the low-frequency DML and classic analog RoF approach utilizing CW laser and MZM for 28 GHz RoF transmission with a seamless 10 m long antenna channel.…”
mentioning
confidence: 99%